2010
DOI: 10.1176/appi.ajp.2009.09070932
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Pharmacogenetics of Antidepressant Response in the GENDEP Project

Abstract: While limited statistical power means that a number of true associations may have been missed, these results suggest that efficacy of antidepressants may be predicted by genetic markers other than traditional candidates. Genome-wide studies, if properly replicated, may thus be important steps in the elucidation of the genetic basis of pharmacological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
248
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 322 publications
(259 citation statements)
references
References 42 publications
(27 reference statements)
6
248
1
Order By: Relevance
“…However, only a small study investigated the potential role of the SNP in MDD and it reported negative findings (Clerici et al 2009), while an additional study reported no association between MDD and the SNP at -634 in a Chinese population (Hong et al 2005). Our findings suggest further investigation of IL-6 polymorphisms in MDD is warranted, particularly as a suggestive signal (rs7801617 SNP) for association with escitalopram response was detected in the IL-6 gene in the Genome-Based Therapeutic Drugs for Depression (GENDEP) genome-wide association study (Uher et al 2010).…”
Section: Interleukin-6mentioning
confidence: 71%
“…However, only a small study investigated the potential role of the SNP in MDD and it reported negative findings (Clerici et al 2009), while an additional study reported no association between MDD and the SNP at -634 in a Chinese population (Hong et al 2005). Our findings suggest further investigation of IL-6 polymorphisms in MDD is warranted, particularly as a suggestive signal (rs7801617 SNP) for association with escitalopram response was detected in the IL-6 gene in the Genome-Based Therapeutic Drugs for Depression (GENDEP) genome-wide association study (Uher et al 2010).…”
Section: Interleukin-6mentioning
confidence: 71%
“…We selected 25 depressed patients (10 females, 15 males) from the Genome-based Therapeutic Drugs for Depression (GENDEP) study who were drug-naïve or had been drug-free for at least 2 wk before assessment (17,36). Controls (7 females, 7 males) were recruited in London through local advertisement and volunteer databases, as part of the GENDEP study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, two SNPs rs17135437 (p = 3.27 × 10 ) in the IL11 gene associated with citalopram response [116].…”
Section: -Hydroxytryptamine Receptor 2amentioning
confidence: 96%